Wolastoqiyik adaptation of the Aaniish Naa Gegii: the Children’s Health and Well-Being Measure - Isabelle Bernard; Joline Guitard; Annie Roy-Charland; Diane Pelletier; Nancy Young (Rural and Remote Health, 2024)
Introduction: Indigenous children in Canada represent one of the fastest-growing pediatric populations and experience severe health inequities. There is an ongoing need for new research on relevant methods to measure the health and wellbeing of Indigenous children that considers the cultural differences between communities. The Aaniish Naa Gegii: the Children's Health and Well-Being Measure (ACHWM) is a self-reported questionnaire that was developed to meet this need and to include the voices of Indigenous children. The purpose of this study was to assess the cultural relevance of the ACHWM for Wolastoqiyik children and to determine what revisions may be needed to ensure that the questions are well understood and culturally appropriate. Methods: We recruited a community-based sample of nine Wolastoqiyik children (ages 8 to 16 years), two caregivers, and a community Elder within the Madawaska Maliseet First Nation community in New Brunswick. Through a process of cognitive debriefing, we probed children's comprehension of the 62 questions of the First Nation French version of the ACHWM. We analyzed the information reported to determine the participants' understandings relative to the other participants and to the original intent of the ACHWM content. Results: Each of the nine children identified at least one item they recommended for revision during the interview. We observed similarities in the suggestions offered by several respondents. A total of 23 questions were considered, and 14 questions (22.6%) were modified, taking into consideration all participants' suggestions. Conclusion: While measures like the ACHWM offer useful information, relying solely on a 'one size fits all' Indigenous questionnaire is insufficient. Our findings underline the importance of having methods that are easily accessible, adaptable, and culturally appropriate for assessing and addressing Indigenous children's unique health and wellbeing. Such information allows clinicians to develop interventions that are culturally relevant, ...